An icon that everyone wants to click: How perceived aesthetic qualities predict app icon successfulness - Henrietta Jylhä; Juho Hamari (Academic Press, 2022)
Mobile app markets have been touted as fastest growing marketplaces in the world. Every day thousands of apps are published to join millions of others on app stores. The competition for top grossing apps and market visibility is fierce. The way an app is visually represented can greatly contribute to the amount of attention an icon receives and to its consequent commercial performance. Therefore, the icon of the app is of crucial importance as it is the first point of contact with the potential user/customer amidst the flood of information. Those apps that fail to arouse attention through their icons danger their commercial performance in the market where consumers browse past hundreds of icons daily. Using semantic differential scale (22 adjective pairs), we investigate the relationship between consumer perceptions of app icons and icon successfulness, measured by 1) overall evaluation of the icon, 2) willingness to click the icon, 3) willingness to download the imagined app and, 4) willingness to purchase the app. The study design was a vignette study with random participant (n = 569) assignment to evaluate 4 icons (n = 2276) from a total of pre-selected 68 game app icons across 4 categories (concrete, abstract, character and text). Results show that consumers are more likely to interact with app icons that are aesthetically pleasing and convey good quality. Particularly, app icons that are perceived unique, realistic and stimulating lead to more clicks, downloads and purchases.